Malaysian bridges and the influence of Sumatran earthquake in bridge design - Ramli, M. Z. (Construction Research Institute of Malaysia, 2016)
The development of bridge design in Malaysia has experienced several changes in its approaches. Bridge inspection identifies the current conditions and the problems in the bridge but seismic vulnerability identifies the expected potential of seismic hazards of a bridge due to lateral seismic forces. The influences and effects of the Sumatran earthquakes toward Malaysian bridges need revised in term of earthquake loading and some modifications and amendments are required for the current code of practice. This paper revealed that the effect from Sumatran earthquakes towards Malaysian bridges is still questionable and a proper site-inspection together with post-earthquake inspections is required to carry immediately. The National Guidelines for Bridge Inspection needs to implement proper schedule with trained and experienced staff for these exercise. Fortunately, the two Penang bridges were designed and considered the seismic loading and taken as examples to highlight the effect of long-distant earthquakes from Sumatra. Both bridges are used almost similar site-specific earthquake response spectra for return periods of 475 years in their designing.